2003
DOI: 10.1007/s00396-002-0835-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of highly loaded platinum nanoparticles on silica by intercalation of [Pt(NH3)4]2+ ions into layered sodium silicate ilerite

Abstract: Highly loaded Pt nanoparticles (20 wt%) on silica were prepared intercalation of [Pt(NH 3 ) ilerite) in air at 380°C for 5 h. Transmission electron microscopy revealed that the size of the Pt particles was in the range 2-5 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…5a), as a result of the agglomeration of Pt nanoparticles during the calcination process. We reported similar findings in our previous study on the intercalation of Na-ilerite with [Pt(NH 3 ) 4 ] 2+ ions [28].…”
Section: Transmission Electron Microscopy ( Tem)supporting
confidence: 90%
“…5a), as a result of the agglomeration of Pt nanoparticles during the calcination process. We reported similar findings in our previous study on the intercalation of Na-ilerite with [Pt(NH 3 ) 4 ] 2+ ions [28].…”
Section: Transmission Electron Microscopy ( Tem)supporting
confidence: 90%
“…This material exhibits a broad range of properties, such as sorption of interlamellar water and polar organic molecules, cation exchange of interlayer sodium cations, intracrystalline swelling, grafting, and transformation into crystalline layered silicic acids by proton exchange [14,15]. Thus, these properties promote the application of Na-magadiite as adsorbents [16], catalysts [17], cation exchangers, or molecular sieves [18]. The interlayer spacing of Na-magadiite, d 001 , changes with water content and exchange sodium ions.…”
Section: Introductionmentioning
confidence: 96%
“…Transition-metal nanoparticles have found some considerable recent use as catalysts in carbon−carbon bond-forming reactions, and, although they are often used in the form of colloidal suspensions, there exists considerable scope for producing heterogeneous catalysts by supporting the nanoparticulate metal on high surface area, solid supports. Palladium and platinum are often the metals of choice in this class of reaction, and a number of recent publications have dealt with the immobilization of nanoparticles of these metals onto silica and alumina surfaces. The composite materials have been prepared using a variety of chemical approaches; for example, Wu et al. incorporated palladium in mesoporous silica during the synthesis of the silica itself, Okitsu et al used a sonochemical approach to deposit Pd particles onto alumina from PdCl 2 , Zhou et al used a novel homogeneous approach via cyclodextrins and an ordered polystyrene bead array to give silicas with bimodal pore distributions, with Pd incorporated into the pore walls, and Choudary et al reduced PdCl 4 2- using hydrazine hydrate onto layered double hydroxide (LDH) supports .…”
Section: Introductionmentioning
confidence: 99%
“…Palladium and platinum are often the metals of choice in this class of reaction, and a number of recent publications have dealt with the immobilization of nanoparticles of these metals onto silica and alumina surfaces. [7][8][9][10][11][12][13][14][15][16][17][18] The composite materials have been prepared using a variety of chemical approaches; for example, Wu et al incorporated palladium in mesoporous silica during the synthesis of the silica itself, 9 Okitsu et al used a sonochemical approach to deposit Pd particles onto alumina from PdCl 2 , 10 Zhou et al used a novel homogeneous approach via cyclodextrins and an ordered polystyrene bead array to give silicas with bimodal pore distributions, with Pd incorporated into the pore walls, 12 and Choudary et al reduced PdCl 4 2using hydrazine hydrate onto layered double hydroxide (LDH) supports. 11 In some cases, the materials produced by these routes have been assessed for their catalytic activity: Choudary et al used their LDH materials as catalysts in the Heck reaction and found higher activities and selectivities than in homogeneous PdCl 2 systems, 11 Clark et al also studied the Heck reaction with mesoporous silicasupported palladium and found a high degree of recyclability with respect to both activity and selectivity, 8 and Mas-Marza et al produced recyclable clay-supported Pd catalysts for the Sonogashira coupling reaction.…”
Section: Introductionmentioning
confidence: 99%